The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3389/fsufs.2020.601004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Plant Growth Promoting Rhizobacteria (PGPR) and Arbuscular Mycorrhizal Fungi (AMF) on Salt Stress Tolerance of Casuarina obesa (Miq.)

Abstract: Salinity is one of the main abiotic stresses limiting plant growth and development. However, the use of salt-tolerant plants combined with beneficial soil microorganisms could improve the effectiveness of biological methods for saline soil recovery. The aim of this study is to identify the Casuarina obesa/ Arbuscular Mycorrhizal fungi (AMF)/Plant Growth Promoting Rhizobacteria (PGPR) association that could be used in salt-land rehabilitation programs. Thus, the plants were grown under greenhouse on sandy soil,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 27 publications
(30 reference statements)
1
21
0
Order By: Relevance
“…Although an increase in plant growth and grain yield was observed when PGPR and AMF are used in combination, several factors such as environmental conditions, soil quality, and the microbial strains used, contribute to variable results. For example, a 128% increase was observed in combined grain yields of finger millet and pigeon pea in intercropping conducted at the Kolli Hills site but not the Bangalore site [ 165 ]. Generally, an increase in crop yield of approximately 30–40% was observed in combined PGPR and AMF inoculation in field studies.…”
Section: Co-inoculation Of Amf and Pgpr Can Mitigate The Effects Of Salinity In Plantsmentioning
confidence: 99%
“…Although an increase in plant growth and grain yield was observed when PGPR and AMF are used in combination, several factors such as environmental conditions, soil quality, and the microbial strains used, contribute to variable results. For example, a 128% increase was observed in combined grain yields of finger millet and pigeon pea in intercropping conducted at the Kolli Hills site but not the Bangalore site [ 165 ]. Generally, an increase in crop yield of approximately 30–40% was observed in combined PGPR and AMF inoculation in field studies.…”
Section: Co-inoculation Of Amf and Pgpr Can Mitigate The Effects Of Salinity In Plantsmentioning
confidence: 99%
“…PGPRs also secrete several growth phytohormones such as auxins, cytokinins, gibberellins and ethylene which improve both root growth and whole plant growth (Lugtenberg and Kamilova, 2009;Dodd et al, 2010;Wani et al, 2013). Furthermore, work carried out in Senegal by Diagne et al (2020) has also shown that inoculation with PGPR and/or Arbuscular Mycorrhizal Fungi (AMF) can improve the salinity resistance of Casuarina obesa plants by increasing their growth parameters. The use of biologically active natural products and microbial extracts could be an important means of increasing soil nutritional status, absorption and improving the efficiency of nutrient use (NPK) by plants (De Pascale et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Among them, the improvement of biostimulant efficiency was taken into consideration. In order to find the appropriate tools capable of exerting the most effective biostimulant activity on plants, many studies focused on the triple interaction of plants, PGPRs, and AMFs [ 98 , 99 ]. The potential beneficial effect of the combination of different types of inocula as plant biofertilizers may depend on their better stability in adverse environmental conditions [ 100 ].…”
Section: Synergistic/additive Effects Between Microbial Biostimulant Product Componentsmentioning
confidence: 99%
“…An enhancement of plant biomass and yield was detected in Arizona cypress, chickpea, wheat, swamp oak, Jerusalem artichoke, and pea plants when inoculated with PGPRs and AMFs, often exhibiting better results than non-inoculated plants or plants inoculated with a single strain [ 98 , 99 , 106 , 110 , 111 , 112 ].…”
Section: Synergistic/additive Effects Between Microbial Biostimulant Product Componentsmentioning
confidence: 99%